A review on management of major insect pests in castor: A review on management of major insect pests in castor - N VINAY; S V S RAJU; S RAMESH BABU; KAMAL RAVI SHARMA (Journal of Oilseeds Research, 2020)
The productivity of castor is affected by different insect pests. Out of which shoot and capsule borer, tobaccocaterpillar and semilooper are having national significance. By adopting IPM practices we can suppress pest level to below economic injury with least damage to agro-ecosystem. This article reviews the damage and integratedmanagement of these pests to reduce risks with respect to human health and environment.